News and Analysis : COVID-19: an economic perspective. (1st August 2020) - Skuse, Benjamin
Abstract: J Doyne Farmer – a physicist who has studied the economic impact of the COVID-19 pandemic – talks to Benjamin Skuse about lockdown easing and the prospects of financial recovery